The influence of anterior and posterior knot placement on hip function after total hip arthroplasty using a modified Dall's approach: a prospective non-randomised comparative study. Issue 4 (July 2022) - Hara, Hiroaki; Fujita, Hiroshi; Okutani, Yuki; Kataoka, Masanao; Harada, Hideto; Murotani, Yoshiki
Background: The direct lateral modified Dall's approach for total hip arthroplasty (THA) provides an excellent vision of the hip joint by osteotomising the greater trochanter (GT). A robust method for the reattachment of osteotomised fragments is essential to prevent complications around the GT. Ultra-high molecular weight polyethylene cables are reported to be useful for reattachment; but the optimal suture method of these cables is unknown. The purpose of this study was to investigate the influence of the knot position on hip function after primary THA. Methods: In a prospective non-randomised study 216 primary THA were included, being scheduled for an operation with a modified Dall's approach. They were divided into 2 groups, anterior (A) and posterior (P) according to the knot position for the GT. Hip function was assessed using the Japanese Orthopaedic Association Hip Disease Evaluation Questionnaire (JHEQ), pain visual analogue scale (VAS), satisfaction VAS and Merle d'Aubigne-Postel hip score at 3 and 6 months postoperatively. A logistic regression analysis was used to investigate factors influenced by the knot position. Results: Patient demographics were comparable between the 2 groups. Differences of the knot position did not affect the radiological failure rate of GT reattachment. Regression analysis showed a significantly positive impact on pain VAS and flexion range at 6 months postoperatively for posterior knot position. Conclusions: For the reattachment of osteotomised fragments, the posterior knot may be superior to the anterior knot.